1999
DOI: 10.2135/cropsci1999.0011183x003900030025x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Multispectral Radiometry Data to Qualitative Data in Turfgrass Research

Abstract: Multispectral radiometry provides a method for assessing plant light reflectance in the visible and near‐infrared ranges. Reflectance of narrow wavelength ranges as well as ratios of different ranges have been highly correlated with absorbency of photosynthetically active radiation, leaf area index (LAI), and plant response to stresses. The objectives of this research were to determine if data obtained by multispectral radiometry might accurately correlate with qualitative data (used as rapid estimates of colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
130
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(151 citation statements)
references
References 0 publications
13
130
1
2
Order By: Relevance
“…MA et al (1996) verificaram relação positiva da reflectância com o teor de clorofila em plantas de milho. TRENHOLM et al (1999) obtiveram uma correlação linear positiva entre reflectância e a análise visual em algumas gramíneas. Essa relação pode ser considerada vantagem da utilização de medidores de reflectância em gramas.…”
Section: Resultsunclassified
“…MA et al (1996) verificaram relação positiva da reflectância com o teor de clorofila em plantas de milho. TRENHOLM et al (1999) obtiveram uma correlação linear positiva entre reflectância e a análise visual em algumas gramíneas. Essa relação pode ser considerada vantagem da utilização de medidores de reflectância em gramas.…”
Section: Resultsunclassified
“…These attributes respond to irrigation, fertilizer application, cultivation, climatic stresses, traffic stress and pests; therefore, turfgrass performance may be dynamic over the season or even during a dry-down between irrigation events. Trenholm et al (1999) and Bell and Xiong (2008) reported on the use of NDVI and other plant stress indices for assessing turfgrass performance.…”
Section: Plant Responsesmentioning
confidence: 99%
“…For spectral reflectance, the normalized difference vegetation index (NDVI) has been the most commonly used plant performance or stress indicator. It correlates well with turfgrass quality (a combination of shoot density, color and uniformity) as affected by quality differences inherent to the species and cultivar, environmental stresses, fertilizer treatments or injury from pests (Trenholm et al 1999;Bell and Xiong 2008). Spectral reflectance can quantify plant response to stress, fertilizer applications or disease pressure, but the actual cause can be known only from a controlled study or by field observation.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, vegetation indices, calculated by combining band of the reflectance spectrum, were correlated with numerous turfgrass canopy parameters. Trenholm et al (1999), Jiang and Carrow (2007), reported on the utilization of normalized difference vegetation index (NDVI) and other spectral reflectance-based plant stress indices for assessing turfgrass performance, while Bell et al (2004) provided a recent review of optical sensing in turfgrass systems. NDVI was useful for detecting growth differences between species (Caturegli et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%